CircRNA DOCK1 Regulates miR-409-3p/MCL1 Axis to Modulate Proliferation and Apoptosis of Human Brain Vascular Smooth Muscle Cells - Ding, Xinmin; Wang, Xiaolong; Han, Li; Zhao, Zhiyu; Jia, Shuai; Tuo, Yuanzhao (Frontiers in Cell and Developmental Biology, 2021)
Background: Intracranial aneurysm is an abnormal expansion in the intracranial arteries, which is associated with growth and apoptosis of vascular smooth muscle cells. Circular RNAs (circRNAs) take part in intracranial aneurysms progression. The purpose of this study is to study the function and mechanism of circRNA dedicator of cytokinesis 1 (circ_DOCK1) in proliferation and apoptosis of human brain vascular smooth muscle cells (HBVSMCs). Methods: HBVSMCs were exposed to hydrogen peroxide (H2O2). Cell proliferation and apoptosis were detected via 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT), flow cytometry and Western blotting for detection of proliferating cell nuclear antigen (PCNA), B cell lymphoma-2 (Bcl-2), Bcl-2-associated X (Bax) and Cleaved poly-ADP ribose polymerase (PARP) expression. Circ_DOCK1, microRNA (miR)-409-3p, and myeloid cell leukemia sequence 1 (MCL1) abundances were examined via quantitative reverse transcription polymerase chain reaction or Western blotting. The target association was assessed by dual-luciferase reporter, RNA pull-down and RNA immunoprecipitation assays. Results: Exposure to H2O2 decreased proliferation and increased apoptosis of HBVSMCs. Circ_DOCK1 expression was reduced in H2O2-treated HBVSMCs. Circ_DOCK1 overexpression rescued H2O2-caused reduction of proliferation and PCNA expression, and attenuated H2O2-induced apoptosis and expression of Bcl-2, Bax and Cleaved PARP. MiR-409-3p was targeted by circ_DOCK1, and upregulated in H2O2-treated HBVSMCs. MiR-409-3p upregulation mitigated the role of circ_DOCK1 in proliferation and apoptosis of H2O2-treated HBVSMCs. MCL1 was targeted via miR-409-3p, and downregulated via H2O2 treatment. Circ_DOCK1 overexpression enhanced MCL1 expression via modulating miR-409-3p. MiR-409-3p knockdown weakened H2O2-induced proliferation reduction and apoptosis promotion via regulating MCL1. Conclusion: Circ_DOCK1 overexpression mitigated H2O2-caused proliferation inhibition and apoptosis promotion in HBVSMCs by modulating miR-409-3p/MCL1 axis.